1996
DOI: 10.1002/(sici)1097-0010(199603)70:3<380::aid-jsfa517>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Commercial Vodkas by Solid-Phase Microextraction and Gas Chromatography/Mass Spectrometry Analysis

Abstract: A reliable method for the characterisation of vodkas has been developed by application of solid‐phase microextraction (SPME) and gas chromatography/mass spectrometry (GCMS). Sixty‐four samples of commercial Canadian and American vodkas, and one sample each of Japanese and German vodkas, were investigated in this study. The procedure yielded reproducible chromatographic profiles. The detected components were ethyl esters of C8 to C18 fatty acids at μg litre−1 levels, various additives and contaminants. Distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 3 publications
1
39
0
1
Order By: Relevance
“…Ng, et al [56] determined that 18 different vodkas could be differentiated according to the raw materials used and the method of production. In this work, ethyl ester levels (fermentation by-products from yeast) were one of the markers used to identify the different spirits [56]. These results were not confirmed by Cai, et al [45] who found that, when examining 12 commercially available vodkas, the levels of volatile congeners could not be correlated to the raw material for fermentation or the geographical origin of the spirit.…”
Section: Role Of Yeastsupporting
confidence: 91%
See 1 more Smart Citation
“…Ng, et al [56] determined that 18 different vodkas could be differentiated according to the raw materials used and the method of production. In this work, ethyl ester levels (fermentation by-products from yeast) were one of the markers used to identify the different spirits [56]. These results were not confirmed by Cai, et al [45] who found that, when examining 12 commercially available vodkas, the levels of volatile congeners could not be correlated to the raw material for fermentation or the geographical origin of the spirit.…”
Section: Role Of Yeastsupporting
confidence: 91%
“…Ng, et al [56] determined that 18 different vodkas could be differentiated according to the raw materials used and the method of production. In this work, ethyl ester levels (fermentation by-products from yeast) were one of the markers used to identify the different spirits [56].…”
Section: Role Of Yeastmentioning
confidence: 99%
“…Traditional raw materials for vodka production were cereals, especially maize and wheat (Lachenmeier et al 2008;Art Maski Company 2010). Currently, other raw materials can be also found on the bottle labels: potatoes, molasses or sugar beet (Ng et al 1996;Lachenmeier et al 2003;Art Maski Company 2010).…”
mentioning
confidence: 99%
“…(Fillipova 1994;Ng et al 1996;Fillipova & Fillipova 1997;Blecha 2008;Mukhin et al 2009;Siříšťová & Melzoch 2009). …”
unclassified
See 1 more Smart Citation